The INDDEX24 Dietary Assessment Platform Compared to Pen and Paper 24-Hour Dietary Recalls: Evidence on Cost, Cost-Effectiveness, and Accuracy From Viet Nam and Burkina Faso. (14th June 2022) - Bell, Winnie; Some, Jerome; Adams, Katie; Bakun, Peter; Colaiezzi, Brooke; Wafa, Sarah; Do, Ha Phuong; Rogers, Beatrice; Coates, Jennifer
Abstract: Objectives: The INDDEX24 Dietary Assessment Platform (INDDEX24) is an integrated dietary research platform that leverages the INDDEX24 Mobile App and the Global Food Matters Database to accelerate food and nutrition research in low- and middle-income countries. The goal in designing INDDEX24 was to increase the collection of actionable dietary data by developing a solution that would reduce the overall cost and time of surveys, while also improving accuracy. Methods: To test the accuracy of INDDEX24, rigorous validation studies were conducted comparing INDDEX24 to pen-and-paper 24 HR, with both evaluated against the benchmark of observer-weighed food records (WFR). These interviews were carried out for a sample of women between the age of 18 and 49 in Burkina Faso (n = 231) and Viet Nam (n = 234). An accompanying cost-effectiveness study measured the time and cost required to perform a 24 HR, the time per interview, and the cost-per-unit of accuracy of INDDEX24 compared to pen-and-paper and the WFR. This study used activity-based costing methods to account for the time and money spent to prepare for the study, implement the survey, and process the 24 HR data to produce usable results. To estimate the time per interview, additional respondents (n = 60) were randomly selected from urban and rural areas, and the time of each interview was recorded. Results: The accuracy of INDDEX24 was the same or slightly better than pen-and-paper when compared to the weighed food record, and varied by country, food group, and nutrient. From a cost perspective, we found that using INDDEX24 reduced the cost by 65 per respondent in Viet Nam where pen-and-paper cost 820 and INDDEX24 cost 755 per respondent, and by 5 per respondent in Burkina Faso where pen-and-paper cost 544 and INDDEX24 cost 539. INDDEX24 was also more cost-effective (i.e., lower cost per unit of relative accuracy) compared to pen-and-paper due to superior accuracy of a composite nutrient intake measure and lower time and personnel costs for survey administration and data entry. Conclusions: The rigorous validation studies in both Viet Nam and Burkina Faso concluded that the use of INDDEX24 reduces the costs and time required to implement 24-hour recall studies, while maintaining or improving data accuracy. Funding Sources: Bill & Melinda Gates Foundation.